Right to Privacy and Electoral Reforms with Special Reference to Data Protection Law in India - Suvek Singh Chauhan (AG Volumes, 2026)
In the year 2017, the Right to Privacy has been recognized as a fundamental right by the Supreme Court of India. In December 2021, by amending the Representation of the People Act 1951, the Indian Parliament made a provision to link Aadhaar card with Voter ID card. Linking of Aadhaar data with Voter ID card is being said to result in violation of the fundamental right to privacy. In the world's largest democratic country, where elections are fought on the basis of caste, religion, regionalism etc., in such a situation, the side effects of linking Aadhaar data with Voter ID card can come out in the form of political profiling of voters. Efforts can be made by political parties to get voter's personal information in their favor in an undemocratic manner. Although a Data Protection Act has recently been passed by the Indian Parliament, some provisions of the present Act give the government privilege of using and storing personal data, due to which doubts are being expressed about the effectiveness of this Act in future. Personal data including health etc. must be protected. Protection of health data through separate legislation as The Digital Information Security in Health Care Act (DISHA) is needed for collection, use, storage, dissemination and transfer of data intra and inter clinical establishment. It is opted for need of specific provisions to control and regulate installation and use of CCTV and Biometric Data collection devices.